(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Hydroponics and Aquaponics areinnovative horticultural techniques that offer efficient, sustainable alternatives to traditional soil-based agriculture. These methods leverage advanced technology to optimize plant growth, conserve resources, and increase crop yields. Hydroponics involves growing plants in a nutrient-rich water solution, eliminating the need for soil. Plants are supported by inert media such as rock wool or clay pellets, which provide stability and facilitate root development. This method allows precise control over nutrient delivery,waterusage, and environmental conditions, leading to faster growth rates and higher yields. Hydroponic systems can be implemented in various forms, including nutrient film technique (NFT), deep water culture (DWC) and drip systems. Aquaponics are integrates hydroponics with aquaculture, creating a symbiotic environment where plants and fish coexist. Fish waste provides an organic nutrient source for the plants, while the plants filter and purify the water for the fish